Repertoire of youth activism in 1970s Hong Kong: The 70s Biweekly and experimental cinema - Lu Pan (Cogent Arts & Humanities)
First published in 1970, The 70s Bi-weekly (hereafter, The 70s) stands out from many other independent magazines in Hong Kong around the same time by its unique ‘action-oriented-ness’. More than a printed magazine whose contents blend radical political theories, social activism, and avant-garde art, the ‘action-oriented’ feature of The 70s is seen in both of its political and cultural actions. This article places The 70s in the context of the production and screening of experimental films in Hong Kong at the time, and discusses two (experimental) films made by the magazine’s editorial board in the 1970s. They are a documentary (1971) that records the ‘Defend Diaoyu Islands’ protests on April 10th of the same year in Hong Kong and an experimental film To the Arty Youths of Hong Kong (1978), imbued with political metaphors and critical sarcasm. Extending Charles Tilly’s (2008) discussion on the repertoire of contentious politics to the cultural dimension, I argue that these films constitute one of their diverse repertoires of social activism. The transformation of the cinematic style from realism to postmodern collage also illustrates a vital shift of the media performativity in their repertoire of dissent.